A Behavioural Approach to Strategic Management - Károly Balaton (Theory, Methodology, Practice, 2023)
The concepts, methods and practices of strategic management have evolved significantly since the beginning of the 20th century. In the 1950s and 60s the use of long-term planning was characteristic. Until the end of the 1980s strategy was perceived as a response to environmental changes. During the 1990s strategy formulation was perceived as a process based on internal resources and capabilities of firms. This radical change with the previously applied concepts was influenced by the accelerated rate of environmental changes. Companies – especially large firms – were unable to change their strategies parallel with changes in their environment. They needed a more stable starting point for developing their strategies. Strategic decision makers intended to make optimal strategic decisions until the end of the 70s. Due to the newly emerged theory of limited rationality it has become accepted as a strong influencing factor of strategic decision-making. Parallel with the above mentioned changes the role of managerial behavioural characteristic had emerged as a more broadly accepted factor in strategic decision-making. In the present paper our intention is to present this development process.